PENDEKATAN MANAJEMEN SEKOLAH DAN PENGAWASAN: KAJIAN PENYALURAN DANA BIAYA OPERASIONAL SEKOLAH (BOS) TINGKAT SEKOLAH MENENGAH PERTAMA - Makruf Makruf; A. Nur Insan; Ilham Safar (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the influence of school management and supervision on the distribution of School Operational Assistance Funds (BOS) at Junior High Schools in Tanjung Selor District, Bulungan Regency. The variables used in this study consist of school management as the first independent variable, supervision as the second independent variable, and BOS fund distribution as the dependent variable. This study employed a quantitative approach using a survey method. The research population consisted of principals, BOS treasurers, and school committee members at private junior high schools in Tanjung Selor District, with a total of 31 respondents. The sampling technique used proportional sampling. Data collection was conducted through questionnaires using a Likert scale. Data analysis was performed using SPSS software, including validity test, reliability test, multiple linear regression analysis, partial test (t-test), simultaneous test (F-test), and coefficient of determination (R²). The results showed that school management did not have a significant effect on the distribution of BOS funds. Supervision also did not have a significant effect on the distribution of BOS funds. Simultaneously, school management and supervision did not significantly influence the distribution of BOS funds. The findings indicate that the effectiveness of BOS fund distribution is more influenced by external factors such as government policies, bureaucratic systems, and fund distribution mechanisms rather than internal school factors.